Metabolic aspects of the regulation of systemic pH - Atkinson, D. E.; Bourke, E. (American journal of physiology. Renal physiology, 1987)
Catabolism of protein produces CO2, NH4+, and HCO3-. Mammals readily lose CO2 through the lungs, but the bicarbonate produced in metabolism of a typical diet (in humans, approximately 1 mol/day from approximately 100 g of protein) would cause alkalosis if not disposed of. Air-breathing animals solve this problem by incorporating NH4+ into organic compounds in which N is not protonated; thus each NH4+ ion loses a proton in the course of the synthesis. These protons serve to titrate HCO3-. In mammals, ureagenesis is the pathway by which protons are liberated from NH4+. The rate of ureagenesis therefore determines the rate of disposal of bicarbonate, and must be an important factor in the maintenance of pH homeostasis. Ammonium ion that is not needed for urea synthesis is packaged into glutamine by the liver. Hepatic glutamine synthetase is localized in the last rank of cells around the pericentral venule; thus glutamine synthetase cannot compete for NH4+ or interfere with the control of pH by urea synthesis. Ammonium excretion in the urine does not represent excretion of acid, and is not stoichiometrically related to renal generation of bicarbonate. The quantitatively major processes by which the HCO3-/CO2 ratio, and hence the pH, is regulated in blood and interstitial fluid are excretion of CO2 through the lungs and disposal of HCO3- as a consequence of ureagenesis in the liver.